HEMODYNAMIC CHANGES IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Radjabova Gulchehra Bahodirovna (Scholar Express Journals, 2022)
This article is written about the smart education trend. The article analyzes the concept of smart education in the developed countries of the world, provides an overview of scientific works on the levels of development of smart education, the transition to a smart society. Also, the thoughts of scientists about smart people are given
Keywords: chronic obstructive pulmonary disease; COPD epidemiology; COPD risk factors